TRANSFORMASI PARADIGMA EKONOMI: ANALISIS KOMPARATIF KAPITALISME DAN EKONOMI SYARIAH DALAM MEWUJUDKAN EKONOMI BERKEADILAN - Khoridah, Aniq (Jurnal Syariah dan Ekonomi Islam, 2026)
The capitalist economic system, which emphasizes individual freedom and unlimited capital accumulation, often generates structural problems such as unequal wealth distribution, resource exploitation, and the marginalization of vulnerable groups. These conditions indicate market failures in achieving social justice and collective welfare. This study aims to comparatively analyze the capitalist economic system and Islamic economics within the framework of attaining economic justice. The research employs a qualitative descriptive approach based on an extensive literature review, analyzing both classical and contemporary sources relevant to the two economic paradigms. The findings reveal that Islamic economics offers a more holistic alternative by integrating moral, social, and spiritual values into economic activities. Islamic instruments such as zakat, infaq, sadaqah, waqf, and the prohibition of riba function as mechanisms for wealth redistribution and the reduction of social inequality. The concept of economic justice in the Islamic perspective is not solely oriented toward economic growth but also emphasizes equity, sustainability, and comprehensive social welfare, ultimately aiming to achieve prosperity and well-being (falah).